Study on the level of somatic development in eighth grade boys - Ciubotaru Mihai; Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
The discipline of physical education and sports through its means leads to the growth and development of the human body. Within the activities carried out during classes, physical education must achieve its objectives, by maintaining an optimal state of health, developing motor skills, learning motor skills and practicing physical exercises. Identifying the anthropometric profile of secondary school students could lead to the optimization of calendar planning and, why not, to the adaptation of educational programs to the discipline of physical education according to somatic development. The main goal is to determine the anthropometric profile of the 8th grade boys from the Iorgu Vârnav Liteanu Technological High School. In the constatative study, I studied specialized works on physical education, used the method of observation, the method of somatic evaluation and systematized the obtained data.